The influence and role of cryptoculture on target congruence in cryptocurrency investment behavior: a theoretical model - Dulisse, Brandon Christopher (Crime, law and social change, 2024)
The unprecedented interest in cryptocurrency-related investments over the past five years has gone from a relatively unknown speculative investment to a mainstream practice and hobby. Novice investors looking for financial gains are now able to buy, sell, and trade cryptocurrency due to social media, smartphone applications, and online forums - all of which disseminate information and build trust in collaborative investment strategies. While many investors have used these platforms for financial gain, others have been the target and victim of relentless scams and forms of fraud. In this paper we argue that despite the advantages of novel financial systems that attempt create access to wealth for a broader base of individuals, the mechanisms behind cryptocurrency marketing, knowledge, and investment are predatory in nature and create a culture designed to pressure and coerce uneducated investors into financial victimhood. Specifically, we present a theoretical model whereby cryptoculture - as we define it - unintentionally produces target congruence of motivated offenders with an excess of suitable targets, further exacerbated by the lack of face-to-face engagement of online encounters. By Articulating a theoretical model should guide future studies in operationalizing cryptoculture and cryptocurrency fraud and prevent future cryptocurrency scams and fraud.